ASSESSING THE ROLE OF WORKFORCE PARTICIPATION, POPULATION SIZE, AND HUMAN DEVELOPMENT IN SHAPING POVERTY IN INDONESIA (2019–2024) - Previta Ridha Putri; Ida Budiarti; I Wayan Suparta (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2025)
This study is intended to analyze TPAK, Population, and HDI on poverty in Indonesia during the 2019–2024 period. Poverty is understood as a multidimensional phenomenon in economic, social, and human development aspects. This study uses a quantitative descriptive approach with a panel data regression analysis method for 34 provinces in Indonesia. The results of data processing showed that partially, TPAK had a positive and significant effect on poverty, which means that increasing labor participation does not necessarily reduce poverty, especially if it is not accompanied by adequate quality of work. The population variable did not have a significant effect, indicating that population size was not the main factor in explaining the variation in poverty between regions. Meanwhile, HDI shows a negative and significant influence on poverty, which proves that the higher the quality of human development, the lower the poverty rate. These findings support Ragnar Nurkse's (1953) theory of the poverty circle, which states that human resource underdevelopment and low productivity are the root causes of recurring poverty. This study recommends that poverty alleviation efforts be focused on improving the quality of human resources and creating productive jobs.